A cross-section analysis of FT3 age-related changes in a group of old and oldest-old subjects, including centenarians’ relatives, shows that a down-regulated thyroid function has a familial component and is related to longevity - Corsonello, Andrea (Oxford University Press, 2010)
Background: several studies suggest that a decreased thyroid activity might be favourable in oldest-old subjects and that subclinical thyroid hyperfunction may be detrimental. Objectives: to verify whether declining levels of circulating thyroid hormones may contribute to longevity. Design: cross-sectional observational study. Setting: all subjects were born in Calabria (southern Italy) and their ancestry in the region was ascertained up to the grandparents. Subjects: six hundred and four home-dwelling subjects (301 females, 303 males), divided into three groups: 278 individuals 60–85 years old; 179 children or nieces/nephews of centenarians who are 60–85 years old; 147 individuals older than 85 years. Methods: thyroid function parameters were measured in the frame of a comprehensive geriatric assessment. Results: FT3 and FT4 levels were negatively associated with age. Lower levels of FT3, FT4 and TSH were found in centenarians’ children and nieces/nephews with respect to age-matched controls. Indeed, being a relative of centenarians qualified as an independent correlate of thyroid parameters. Conclusions: age-related subtle thyroid hypofunction (either due to a familial component or due to a reset of the thyroid function occurring between the sixth and the eighth decade of life) appears to be related to longevity.